2006
DOI: 10.1002/dvdy.20819
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of SMAD2 expression prevents murine palatal fusion

Abstract: Transforming growth factor (TGF)-beta 3 is known to regulate the disappearance of murine medial edge epithelium (MEE) during palatal fusion. Our previous studies showed that SMAD2, a TGF-beta signaling mediator, was expressed and phosphorylated primarily in the MEE and that SMAD2 phosphorylation in the MEE was temporospatially regulated by TGF-beta 3. The goal of this study was to examine the requirement for SMAD2 to complete the developmental events necessary for palatal fusion. SMAD2 expression was inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…This portrays a major discovery in this system, because LEF1 has most commonly been described as being activated by ␤-catenin, as demonstrated in traditional Wnt signaling. These data are justified by previous findings that Wnt-knockout mice show no evidence of palatal clefting, whereas LEF1- (Galceran et al, 1999) and TGF␤3- (Taya et al, 1999) Journal of Cell Science 120 (9) findings of Smad2 knockdown by small interfering RNA (siRNA) in preventing palatal confluence (Shiomi et al, 2006) further support these data. Why ␤-catenin remains in the cytoplasm during palatal EMT remains to be determined.…”
Section: Discussionsupporting
confidence: 57%
“…This portrays a major discovery in this system, because LEF1 has most commonly been described as being activated by ␤-catenin, as demonstrated in traditional Wnt signaling. These data are justified by previous findings that Wnt-knockout mice show no evidence of palatal clefting, whereas LEF1- (Galceran et al, 1999) and TGF␤3- (Taya et al, 1999) Journal of Cell Science 120 (9) findings of Smad2 knockdown by small interfering RNA (siRNA) in preventing palatal confluence (Shiomi et al, 2006) further support these data. Why ␤-catenin remains in the cytoplasm during palatal EMT remains to be determined.…”
Section: Discussionsupporting
confidence: 57%
“…How exactly these three ligands differ in downstream signaling potential remains to be defined, as they all signal through Smad proteins. Whereas they all have the potential to use both Smad2 and Smad3, recent evidence has shown that TGF-␤3 primarily uses Smad2 as its R-Smad protein during EMT (Nawshad and Hay, 2003;Shiomi et al, 2006). Therefore, it is tempting to hypothesize that TGF-␤1 and TGF-␤2 primarily use Smad3 as their R-Smad during EMT.…”
Section: Discussionmentioning
confidence: 99%
“…When Smad2 is inhibited during mouse palate development, the MES is not degenerated (Shiomi et al 2006). Snail is associated with cell survival and cell movement during palatogenesis (Carver et al 2001;Nieto 2002;Barrallo-Gimeno and Nieto 2005) and is regulated by Tgf-b-mediated Smad2 (Martinez-Alvarez et al 2004).…”
Section: Mir-200b Modulates E-cadherin and Tgf-b-mediated Smad2 And Smentioning
confidence: 99%